1991
DOI: 10.1097/00000658-199106000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopie Cholecystectomy Treatment of Choice for Symptomatic Cholelithiasis

Abstract: Our initial experience with laparoscopic cholecystectomy (LC) for symptomatic cholelithiasis has involved 152 patients. Patient age ranged from 17 to 83 years; most were female (78%). Their average weight was 170 pounds (range, 75 to 365 lbs.). Twenty-two per cent had a single gallstone, while 9% had two to three stones and 64% had more than three stones. Exclusion criteria initially included upper abdominal scarring, severe acute cholecystitis, choledocholithiasis, and inability to tolerate general anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
147
1
11

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(167 citation statements)
references
References 6 publications
8
147
1
11
Order By: Relevance
“…In this study the mean length of hospitalization was 1.6 days, which was comparable with the similar studies (1 -4 days) (6,7,(11)(12)(13)(17)(18)(19). Some factors can influence the operative time, such as acute phase of cholecystitis, higher BMI level, previous upper abdominal surgery, male gender, and surgical expertise.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study the mean length of hospitalization was 1.6 days, which was comparable with the similar studies (1 -4 days) (6,7,(11)(12)(13)(17)(18)(19). Some factors can influence the operative time, such as acute phase of cholecystitis, higher BMI level, previous upper abdominal surgery, male gender, and surgical expertise.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the mean operative time was 70 minutes, which was fair compared with other studies. Similar studies have reported different mean operative time ranging from 61 minutes to 149 minutes (7,12,18,20).…”
Section: Discussionmentioning
confidence: 64%
“…From the beginning, laparoscopic cholecystectomy (LC) has been the pacemaker of this development. Elective LC, using the pneumoperitoneum or wall-lifting techniques, has become the gold standard for symptomatic cholelithiasis and the first choice for treatment of this disease in nearly all surgical clinics (Schirmer et al 1991;Kitano et al 1993;Niomiya et al 1998;Ogawa et al 2001). Therefore, laparoscopic cholecystectomy is the most common minimally invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, with the development of greater technical skills and superior laparoscopic instruments, the number of surgical teams that apply laparoscopic cholecystectomy first in acute cholecystitis patients is increasing. While laparoscopic cholecystectomy has gained a leading role in the treatment of acute cholecystitis despite its reportedly high rates of conversion to open surgery, the optimal timing for laparoscopic cholecystectomy in patients with acute cholecystitis has been a matter of controversy during the few past decades.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elderly patients who had more general risk factors and were at an increased surgical risk, as well as those with acute cholecystitis of a greater severity, were selected for PTGBD. Spira et al 13 categorized severe cholecystitis-induced symptoms and advanced age as indications for PTGBD prior to laparoscopic cholecystectomy. Interestingly, the average body temperature ( o C) was 37.39±0.9 in the PTGBD group and 36.90±0.4 in the non-PTGBD group (p=0.001).…”
Section: Discussionmentioning
confidence: 99%